The Effectiveness of the Thinking Acceleration Model in the Achievement and the Acquisition of Grammatical Concepts for Fifth-Grade Students in the Grammar Subject - Natiq Saeed Ghayyib (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The researcher adopted the experimental method with partial control for the two research groups, and the research sample consisted of (60) students. The researcher rewarded the two research groups with grades of the fourth grade, and he determined the behavioral goals and teaching plans. The results showed the superiority of the thinking acceleration model for the experimental group in the achievement test and the acquisition of grammatical concepts for the grammar subject over the control group. In light of that, the researcher puts forward a number of proposals that may contribute to the development of methods of teaching grammar in all stages.